A Cognitive Study Of Negative Transfer Of English Prepositions Made By Vietnamese Learners - Th.S Trần Tín Nghị (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Many current linguists have been interested in whether cognition has any influence on foreign language acquisition. A large number of research have been conducted on L1 transfer; however, the grounds for applying Cognitive Linguistics to language transfer continue to focus on surface structures of the mother tongue and target languages, rather than the underlying causes - the cognition of language users. The purpose of this thesis is to investigate the cognitive factors that influence the usage of English prepositions by Vietnamese learners of English. The author presented how Vietnamese learners of English expressed prepositional meanings from the perspective of Cognitive linguistics and which factors negatively impacted the way Vietnamese learners of English used prepositions. An online survey investigating negative L1 transfer on the use of English prepositions among Vietnamese learners of English was distributed to English learners. Two thousand, eight hundred and thirty-one respondents of differing proficiency levels, qualifications, locations, ages, and biological sexes were surveyed. Analysis of the responses showed that negative L1 transfer was associated with the respondents’ cognition. Their personal perception of the world and language influenced their L2 production. An empirical experiment using an AI chatbot (a form of Facebook Messenger) was also included in the survey to check whether the learning environment contributed to language transfer or not. The author built a speaking and writing assignment corpus from Preparatory Courses for VSTEP to confirm study results. The study results indicated that learners’ L1 cognition played a significant role in affecting learners’ L2 competence, of which negative conceptual transfer made up a sizeable proportion. In particular, the Vietnamese cognition of space (M < 41.47) was responsible for negative L1 transfer to the target language (English). Gender and other non-linguistic factors also contributed to language transfer on the quality of L2 communication with the sig. < 0.05. This study recommends that language teachers take students’ L1 conceptual transfer into account when planning lessons in order to prevent some predictable mistakes in their L2 usage. Linguists, translators, and interpreters are supposed to understand the relevant L1 conceptual transfer to improve their L2 production in their work.